Analisis keterampilan guru dalam mengadakan variasi pada pembelajaran ips kelas iv sd - Tyas, Pertiwi Dyah Musthikaning; Marmoah, Sri; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2021)
This study aims to describe the teacher skills conducting variations in social studies learning. This research are descriptive qualitative. This research was conducted at SD Negeri Dukuhan Kerten No. 58. The subject of this research is 4th grade teacher. Data collection techniques used observation, interview, questionnaires and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of research showed that the 4th grade teacher had implemented a variety of social studies learning well, but the variations in the use of learning media were still less visible. The variations made by the teacher were variations in teaching styles, variations in the use of learning media, and variations in student interactions and activities. The conclusion of research is the teacher skills conducting variations in social studies learning are good.